Neonatal anthropometric indicators of infant growth and mortality in Burkina Faso - Mamadou Bountogo; Ali Sié; Alphonse Zakane; Guillaume Compaoré; Thierry Ouédraogo; Elodie Lebas; Kieran Sunanda O’Brien; Thomas M Lietman; Catherine E Oldenburg (Public Health Nutrition, 2024)
Abstract